2010
DOI: 10.1016/j.molcel.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

CpG Islands Recruit a Histone H3 Lysine 36 Demethylase

Abstract: SummaryIn higher eukaryotes, up to 70% of genes have high levels of nonmethylated cytosine/guanine base pairs (CpGs) surrounding promoters and gene regulatory units. These features, called CpG islands, were identified over 20 years ago, but there remains little mechanistic evidence to suggest how these enigmatic elements contribute to promoter function, except that they are refractory to epigenetic silencing by DNA methylation. Here we show that CpG islands directly recruit the H3K36-specific lysine demethylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
312
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(340 citation statements)
references
References 46 publications
24
312
0
4
Order By: Relevance
“…Recent study has suggested that depletion of H3K36me2, along with the deposition H3K4me3, at CpG-rich promoter helps establish a platform for the assembly of gene regulatory machinery [112]. Removal of H3K36me2 can be directed by the JmjC domain-containing demethylases, Kdm2a and Kdm2b (also called Jhdm1a/Fbxl11 and Jhdm1b/Fbxl10, respectively).…”
Section: H3k36 Methylation H3k36 Methylation Especiallymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has suggested that depletion of H3K36me2, along with the deposition H3K4me3, at CpG-rich promoter helps establish a platform for the assembly of gene regulatory machinery [112]. Removal of H3K36me2 can be directed by the JmjC domain-containing demethylases, Kdm2a and Kdm2b (also called Jhdm1a/Fbxl11 and Jhdm1b/Fbxl10, respectively).…”
Section: H3k36 Methylation H3k36 Methylation Especiallymentioning
confidence: 99%
“…Removal of H3K36me2 can be directed by the JmjC domain-containing demethylases, Kdm2a and Kdm2b (also called Jhdm1a/Fbxl11 and Jhdm1b/Fbxl10, respectively). ESCs lacking Kdm2a appear to be normal in self-renewal [71,112], while Kdm2b-deficient ESCs maintain the expression of pluripotency genes, but display a skewed lineage commitment upon differentiation (He and Zhang, unpublished data).…”
Section: H3k36 Methylation H3k36 Methylation Especiallymentioning
confidence: 99%
“…2,[6][7][8] Although H3K36me3 and H3K36me2 are associated mainly with active gene bodies, where they prevent spurious transcription initiations, H3K36me2 has been also found to be associated with transcriptionally active gene promoters and its removal by KDM2A leads to transcriptional repression of such promoters. 1,[9][10][11][12][13][14][15][16][17][18][19] The short demethylation-defiecient KDM2A isoform KDM2A-SF lacks the N-terminal demethylation domain, but it retains the ability to bind to CpG islands.…”
Section: Discussionmentioning
confidence: 99%
“…KDM2A, also known as FBXL11 or JHDM1A, is a DNA binding protein that binds directly to CpG islands in gene promoters and represses the activity of these promoters by demethylating their H3K36me2 through its N-terminal demethylase JmjC domain. 2,[6][7][8] Although methylation of H3K36 is known to repress spurious transcription initiation in bodies of transcriptionally active genes and it has been detected on promoters of transcriptionally repressed genes, H3K36me2 has been also shown to be associated with transcriptionally active promoters. 2,[9][10][11][12][13][14][15] Demethylation of promoter-associated H3K36me2 by KDM2A has been shown to result in transcriptional repression of these promoters, whereas a loss of KDM2A leads to increased levels of promoter-associated H3K36me2 and transcriptional de-repression of these promoters.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of DNA methylation, both methylated and unmethylated CpG dinucleotides are recognized by specific binding proteins. MBD (methyl‐binding domain‐containing) and methyl CpG‐binding proteins (MECP) recognize methylated DNA 40, while unmethylated CpG at TSSs are recognized by the H3K36 demethylase KDM2A 41, providing further evidence for the interplay between histone post‐translational modifications and DNA methylation. The bromodomain‐containing protein BRD4, which is found as a translocation product with the nuclear protein in testis (NUT) protein in human squamous carcinoma, has been targeted using bromodomain inhibitors 42.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%